Self-healing epoxy nanocomposites via reversible hydrogen bonding. (15th January 2019) - Guadagno, L.; Vertuccio, L.; Naddeo, C.; Calabrese, E.; Barra, G.; Raimondo, M.; Sorrentino, A.; Binder, W.H.; Michael, P.; Rana, S.
Abstract: The development of high performance self-healing composites is still at an early stage due to the difficulty to integrate self-healing mechanisms in their structure by applying current manufacturing processes. Here, the authors propose structural self-healing resins based on dynamic hydrogen bonds capable to overcome many current industrial limitations. Hydrogen bonding moieties, such as barbiturate and thymine, able to act as reversible healing-elements by their simultaneous donor and acceptor character, can be covalently linked to multi-wall carbon nanotubes (MWCNTs) to generate self-healing nanocomposites. The so functionalized MWCNTs, embedded in a rubber-toughened epoxy formulation, lead to reversible MWCNTs-bridges through the matrix due to strong attractive interactions between the rubber phase, finely dispersed in the matrix, and MWCNT walls. Healing efficiencies have been assessed for the nanocharged epoxy formulation loaded with 0.5% wt/wt of MWCNTs decorated with barbituric acid and thymine groups. For both functional groups, healing efficiencies higher than 50% have been found. Dynamic mechanical analysis (DMA) evidences an enhancement in epoxy chains movements due to micro/nano domains of the rubber phase enabling self-healing behavior by recovering the critical fracture load. Results from this study may promote the wide development of safe and cost-efficient self-healing composites in aeronautical, automotive, civil engineering and wind power industries. Graphical abstract: Highlights: Hydrogen bonding moieties, able to act as reversible healing-elements, have been covalently linked to MWCNTs. Functionalized MWCNTs, embedded in a rubber-toughened epoxy resin, lead to reversible MWCNTs-bridges through the matrix. Healing efficiencies have been assessed for nanocharged epoxy formulations with 0.5% wt/wt of functionalized MWCNTs. Healing efficiencies higher than 50% have been found in epoxy matrices loaded with 0.5% wt/wt of modified MWCNTs. Results from this study allow new design concepts for self-healing structures.